Design of Deep Eutectic Systems: Plastic Crystalline Materials as Constituents - Alhadid, Ahmad; Nasrallah, Sahar; Mokrushina, Liudmila; Minceva, Mirjana (Molecules, 2022)
Deep eutectic solvents (DESs) are a class of green and tunable solvents that can be formed by mixing constituents having very low melting entropies and enthalpies. As types of materials that meet these requirements, plastic crystalline materials (PCs) with highly symmetrical and disordered crystal structures can be envisaged as promising DES constituents. In this work, three PCs, namely, neopentyl alcohol, pivalic acid, and neopentyl glycol, were studied as DES constituents. The solid–plastic transitions and melting properties of the pure PCs were studied using differential scanning calorimetry. The solid–liquid equilibrium phase diagrams of four eutectic systems containing the three PCs, i.e., L-menthol/neopentyl alcohol, L-menthol/pivalic acid, L-menthol/neopentyl glycol, and choline chloride/neopentyl glycol, were measured. Despite showing near-ideal behavior, the four studied eutectic systems exhibited depressions at the eutectic points, relative to the melting temperatures of the pure constituents, that were similar to or even larger than those of strongly nonideal eutectic systems. These findings highlight that a DES can be formed when PCs are used as constituents, even if the eutectic system is ideal.
CRIS-Team Scopus Importer:2022-10-28
Keywords: deep eutectic solvents; differential scanning calorimetry; green solvents; melting properties; solid–liquid equilibria; solid–solid transition